Idarucizumab Improves Outcome in Murine Brain Hemorrhage Related to Dabigatran - Na, Shin-Young; Mracskó, Eva; Veltkamp, Roland (Annals of neurology, 2015)
Lack of specific antidotes is a major concern in intracerebral hemorrhage (ICH) related to direct anticoagulants including dabigatran (OAC‐ICH). We examined the efficacy of idarucizumab, an antibody ...
Gesehen am 10.08.2020